SYNTHESIS AND IN-VITRO ANTIMICROBIAL STUDIES OF SOME NEW PYRAZOLONES - Gupta, Poonam; Gupta, Jitendra Kumar; Bansal, Shivani; Halve, A. K. (International Journal of Current Pharmaceutical Research, 2015)
In the present scenario antibacterial agents are the greatest contribution of chemotherapy. They have great importance in the developing countries where infectious diseases predominate. Pyrazolone derivatives are an important class of heterocyclic compounds that occur in many drugs and synthetic products. It has a particular value due to their broad spectrum of biological activities and their utility as synthetic tools in the design of various bioactive molecules. It is also exhibited analgesic, antipyretic and anti-inflammatory activity. In the present study, a series of 3-methyl-N-(substituted phenyl)-5-oxo-4,5-dihydro-1H-pyrazole-1-carbothioamide (3a-g) were synthesized by the reaction of thiosemicarbazides (1) and ethylacetoacetate (2) in DMF. The synthesized compounds were characterized on the basis of IR, 1H-NMR, 13C-NMR and elemental analysis. All synthesized compounds were screened for antimicrobial activities using disc diffusion technique against four bacterial pathogens viz Staphylococcus aureus, Escherichia coli, Bacillus anthracis and Pseudomonas aeruginosa & two fungal pathogens namely Candida albicanes, Aspergillus niger. Chloramphenicol and Fluconazole were used as standard drug respectively. The compounds exhibit moderate activity.